Mary Shelley’s migraines and fatal stroke: some observations on their primary cause - Galassi, Francesco Maria; Varotto, Elena; Nerlich, Andreas; Bianucci, Raffaella (Acta Biomedica Atenei Parmensis, 2022)
In this article the origins of Mary Shelley’s neurological and cerebrovascular problems are described. Through a reanalysis of her biography, her early health issues caused by a dermatological condition, potentially eczema, psoriasis or chickenpox, are related, thanks to current biomedical knowledge, to her migraines and strokes, including the one that killed her.